Understanding the current and future usage of donor human milk in hospitals: An online survey of UK neonatal units - Natalie S. Shenker; Samantha Griffin; Jonathan Hamill‐Keays; Merran Thomson; Judith Simpson; Gillian Weaver (Wiley, 2023)
Abstract The use of donor human milk (DHM) where there is a shortfall of maternal milk can benefit both infant and maternal outcomes but DHM supply is not always assured. This study aimed to understand current DHM usage in UK neonatal units and potential future demand to inform service planning. An online survey was disseminated to all UK neonatal units using Smart Survey or by telephone between February and April 2022 after development alongside neonatal unit teams. Surveys were completed by 55.4% of units (108/195) from all 13 Operational Delivery Networks. Only four units reported not using DHM, and another two units only if infants are transferred on DHM feeds. There was marked diversity in DHM implementation and usage and unit protocols varied greatly. Five of six units with their own milk bank had needed to source milk from an external milk bank in the last year. Ninety units (84.9%) considered DHM was sometimes (n = 35) or always (n = 55) supportive of maternal breastfeeding, and three units (2.9%) responded that DHM was rarely supportive of breastfeeding. Usage was predicted to increase by 37 units (34.9%), and this drive was principally a result of parental preference, clinical trials and improved evidence. These findings support the assumption that UK hospital DHM demand will increase after updated recommendations from the World Health Organization (WHO) and the British Association of Perinatal Medicine. These data will assist service delivery planning, underpinned by an ongoing programme of implementation science and training development, to ensure future equity of access to DHM nationally.